(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article touches upon the peculiarities of types of situation in acquiring Kazakh as a second language. The methods of speaking formation of foreign students, who study the Kazakh language, are considered and the analysis of psychological backgrounds of teaching speaking is given. A prominent place among conditions required for speaking is given to situations and their components. The academic process cannot reflect all really existing situations, therefore, it is proposed to model academic communicative situations which imitate real speech communication. In the article, various methodic recommendations are provided, which correspond to various stages of education. The focus is not only on the linguistic form of expression but also on the content form. Interactive forms, the use of dialogues and polylogues are proposed for teaching speaking. The system of exercises, provided in the article, contributes to development of oral communication.